The Effect of Liquidity, Leverage, Profitability and Inventory Intensity on Tax Aggressiveness - Adelia, Dian Nuningrum; Andayani, Sari (Dinasti Publisher, 2025)
Taxes are one of the main sources of state revenue that play a vital role in supporting national development as well as providing various public services and facilities to the public. A corporation as a tax subject is obligated to pay taxes on its taxable income. Since this duty is frequently viewed as a burden that lowers earnings, some businesses actively arrange their taxes to minimize the amount of taxes that must be paid. This study aims to investigate the relationship between tax aggression and liquidity, leverage, profitability, and inventory intensity. Using secondary data from financial documents, this study employed a quantitative methodology. Purposive sampling techniques were used to choose 38 firms, or 114 data points, from the 76 companies that were listed on the Indonesia Stock Exchange between 2021 and 2023, which made up the research population. Multiple linear regression is the analytical method that is employed. Research results indicate that all four variables liquidity, leverage, profitability, and inventory intensity correlated negatively to tax aggressiveness. It is recommended that future research involve larger numbers of samples and longer observation periods to obtain more representative and accurate results.